(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Survey of the rate of occult cervical lymph node metastasis and identification of associated factors in high-risk parotid cancer patients with cervical lymphadenopathy. Methods: We conducted a retrospective descriptive case-series study of clinically node-negative patients with high-risk parotid gland carcinoma who underwent total parotidectomy combined with elective neck dissection at the Department of Head and Neck Surgery - Otorhinolaryngology, Ho Chi Minh city Oncology Hospital, from January 1, 2022 to July 1, 2025. Results: A total of 42 patients with high-risk parotid gland carcinoma underwent surgery. The mean age was 50.6 years (95% CI: 16-80 years), with a female-to-male ratio of 1.2/1. Most tumors were at an advanced clinical stage (cT3, cT4), accounting for 83.3% of cases. High-risk histopathologic subtypes comprised 57.1% of the cohort. The postoperative rate of histologically confirmed cervical lymph node metastasis was 40.5%. An independent association was found between high-risk histopathologic subtype and cervical lymph node metastasis rate (p = 0.024). Conclusions: Cervical lymph node metastasis is common in high-risk parotid gland carcinoma. Elective neck dissection should be considered, particularly in cases with high-risk histopathologic features.